1997
DOI: 10.1002/(sici)1096-8652(199707)55:4<193::aid-ajh5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tissue factor antigen levels in capillary whole blood and venous blood: Effect of tissue factor on prothrombin time

Abstract: To measure the amount of tissue factor released during specimen collection and its potential effect of shortening the prothrombin time, we measured tissue factor and prothrombin time in twenty-three paired venous and capillary blood samples from anticoagulated patients and in ten paired samples from controls. We also compared venous prothrombin time determined by a plasma-based assay with venous and capillary prothrombin time determined with a whole blood assay. Venous specimens were obtained using a two-syrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A venous blood sample (0.109 mol/L (3.2 %) trisodium citrate) from the same patient was sent by mail to Akershus University Hospital (Akershus, Norway) and analyzed by the assigned comparison method. Previous studies have demonstrated good agreement between venous and capillary blood PT times [8]. All the participants received a feedback report illustrating their results in comparison with those of other office laboratories and the target value.…”
Section: Split-sample Surveymentioning
confidence: 99%
“…A venous blood sample (0.109 mol/L (3.2 %) trisodium citrate) from the same patient was sent by mail to Akershus University Hospital (Akershus, Norway) and analyzed by the assigned comparison method. Previous studies have demonstrated good agreement between venous and capillary blood PT times [8]. All the participants received a feedback report illustrating their results in comparison with those of other office laboratories and the target value.…”
Section: Split-sample Surveymentioning
confidence: 99%